Penerapan Model Multisensori untuk Meningkatkan Keterampilan Berbicara Mahasiswa dalam Menyampaikan Pidato Persuasif - Purlilaiceu, Purlilaiceu (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to determine the teaching and learning process by applying a multisensory model to students' speaking skills in delivering persuasive speeches. The research method used was classroom action research (CAR) with two cycles in which each cycle consisted of two actions. Data obtained from this study include observations, performance tests, and interviews. The results showed that the teaching and learning process of speaking skills in greeting persuasive speeches by applying multisensory models can increase student activity and involvement in each cycle. The average activity of students in the first cycle reached 72.00% and increased in the second cycle reached 86.00%. Speaking skills in this matter of delivering persuasive speeches have been shown to be evident in the first cycle of student performance reaching 71.70% and in silus II reaching 80.00%. In addition, the results of the interviews showed that students were interested in applying the multisensory model because it could make it easier for students to deliver persuasive speeches.